"As Long As We Have the Mine, We'll Have Water": Exploring Water Insecurity in Appalachia. Issue 1 (27th July 2020) - Wies, Jennifer R.; Mays, Alisha; Collins, Shalean M.; Young, Sera L.
ABSTRACT: Water insecurity is a condition when affordability, reliability, adequacy, or safety of water is significantly reduced or unattainable resulting in jeopardized well‐being. Water insecurity co‐occurs with poverty and social and economic exclusion. It is gaining increasing attention from the scholarly community, but most work has focused on low‐ and middle‐income countries. In this article, we explore water insecurity in Appalachian Kentucky. Throughout the Appalachia region, water access and quality are compromised as a result of contamination from extractive industries (such as coal mining) and failure of infrastructure investment. The water problems have been reported by journalists, activists, and social and natural scientists who describe a reliance on discolored, sulfuric, and sometimes toxic water to meet household needs. In this article, we build upon applied anthropology studies of human–environment interaction to answer the exploratory question: "Do patterns about water acquisition and consumption exist in Appalachian Kentucky?" Our methodologies included participant observation and informal go‐along interviews at three sites based on convenience. The results are presented with rich ethnographic description, and reveal that preferences are influenced by the costs of water, the availability of water from different sources (wells, taps, mines, rain capture, etc.), and historic use patterns. We call for a culturally and historically informed approach to understand and measure water insecurity and water improvement efforts in Appalachia. Our ability to characterize water insecurity in low‐resource settings in the United States will allow for better understanding and visibility of the water‐related experiences of marginalized communities and serve as powerful policy inputs.